Klasifikasi Channel Youtube Indonesia Menggunakan Algoritma C4.5 - Ardi Ramadhan Sukma; Riqadri Halfis; Ady Hermawan (Universitas Bina Sarana Informatika, 2019)
In the current era, social media is very influential in our lives whether from Instagram, Twitter, Youtube, or others. One of them is social media Youtube which has a very important role for the public, even though public figures. Youtube provides very interesting content for those who have a channel because they have an assessment of Video Upload, Subscriber, Video Viewers. Even Youtube provides an opportunity for Youtube channels that install Google AdSense to be paid to the owner of the Channel. Youtube Channel ratings can be rated from Video Upload, Subscriber, Video Viewers. From the Youtube data processing data can be done. One data processing technique that can be used in the process is classification. Classification is a data processing technique that divides objects into classes according to the desired number of classes. And using the C4.5 algorithm in the classification process. Who can determine the Youtube Channel especially Indonesia with a Very Good or Good ratio